QUALITY: how far does it go, in a company? - Silva, Alexandre Henrique da; Rodolpho, Daniela (Revista Interface Tecnológica, 2022)
On the world stage, it is seen that there is extreme business volatility and that consumer demands regarding the expectation generated by something are very intense. Increasing challenges make companies move towards the superiority of their enterprise - to coexist in a "predatory" market - through means of co-option and correction of errors and process failures, in search of the right quality. Therefore, the present work to be evaluated aims to address the complexity of the quality issue and its determination through quality management or total quality. In the interpretation that the author takes to this article, it is understood that companies - in a general context - have limitations and internal (and even external) conflicts for not having very well clarified goals when it comes to promoting the quality of their product, service, performance of human, financial, marketing, and technological resources. The importance of management based on the structure of quality of results within an organization must be taken seriously, a fact that often does not occur at the beginning, having a very shallow idea of ​​the role and relevance of the quality department in the growth and in the necessary adjustments for any means held in the operation of a company. Through this, the objective of this article is to expose the areas that are linked to quality management and detail its importance in the process of continuous improvement and what is the role of human capital.
Keywords: Volatility; Quality; Results